The pomegranate (Punica granatum L.) draft genome dissects genetic divergence between soft‐ and hard‐seeded cultivars. Issue 4 (6th November 2019) - Luo, Xiang; Li, Haoxian; Wu, Zhikun; Yao, Wen; Zhao, Peng; Cao, Da; Yu, Haiyan; Li, Kaidi; Poudel, Krishna; Zhao, Diguang; Zhang, Fuhong; Xia, Xiaocong; et al.
Summary: Complete and highly accurate reference genomes and gene annotations are indispensable for basic biological research and trait improvement of woody tree species. In this study, we integrated single‐molecule sequencing and high‐throughput chromosome conformation capture techniques to produce a high‐quality and long‐range contiguity chromosome‐scale genome assembly of the soft‐seeded pomegranate cultivar 'Tunisia'. The genome covers 320.31 Mb (scaffold N50 = 39.96 Mb; contig N50 = 4.49 Mb) and includes 33 594 protein‐coding genes. We also resequenced 26 pomegranate varieties that varied regarding seed hardness. Comparative genomic analyses revealed many genetic differences between soft‐ and hard‐seeded pomegranate varieties. A set of selective loci containing SUC8‐like, SUC6, FoxO and MAPK were identified by the selective sweep analysis between hard‐ and soft‐seeded populations. An exceptionally large selective region (26.2 Mb) was identified on chromosome 1. Our assembled pomegranate genome is more complete than other currently available genome assemblies. Our results indicate that genomic variations and selective genes may have contributed to the genetic divergence between soft‐ and hard‐seeded pomegranate varieties.